MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF MATEMATIS SISWA SMP MELALUI MODEL PEMBELAJARAN PROBLEM POSING - Jajang Rahmatudin; Rifqi Hidayat; Dede Maf’ul Ma’lani (Integral : Pendidikan Matematika, 2017)
This research is motivated by the poor ability of creative thinking mathematically, still infrequent use of the learning model and the lack of involvement of the student in the learning. The purpose of this study was to determine the increase mathematical thinking ability of students whose learning model Problem Posing with conventional learning. This study is a quasi-experimental research. The study design used Nonequivalent Control Group Design and its population is a class VII student of Al-Falah Depok Cirebon in academic year 2016/2017. Sample collection technique is purposive sampling, sample involving students of class VII, that 34 students of class VII A as an experimental class and class VII B of the 36 students as the control class. The results showed that: (1) There are differences in creative thinking ability of students learning mathematical model Problem Posing with students whose learning conventionally. (2) Enhancement of creative thinking ability of students learning mathematical model posing problem better than the increase creative thinking ability of students learning mathematical conventionally. Keywords: Problem Posing, creative thinking mathematically, experimental method.